Pengaruh lama pemakaian KB suntik DMPA terhadap kenaikan berat badan - Uun Undiarti; Suherni Suherni; Siti Tyastuti (Jurnal Kesehatan Ibu dan Anak, 2015)
KB acceptors active injection in Bantul rank first in DIY with total amount of 50.5%, the highest rank of 6061 people (50.1%) occurred in Sewon (Ministry of Health, 2011). KB injectable DMPA has one side effect, that is weight gain. Based on a preliminary study of the 20 respondents in Puskesmas Sewon I, 70% of their body weight increased along with duration of use. Problem arising from the increase in body weight is a health issue. A long-term utilization of hormonal contraception always generates the bad side effect for health. DMPA injectable contraceptive are acceptable as hormonal contraception, but maximum usage limit is 10 times injection or 2.5 years (Suroso, 2011). The purpose of the research is to knew the influence between duration of use of DMPA injections (KB) to weight gain in Puskesmas Sewon I, Bantul 2012. Observational analytic study with cross-sectional approach. Population study are all KB acceptors DMPA injection at Puskesmas Sewon I, Bantul in 2012 amounted to 323 subjects. Samples were taken at consecutive sampling of medical records for the date April 4th to June 14th 2012 amounted ti 179 subjects. Kendall-tau (t) method used for the data analysis. Most of the subject had used DMPA injections KB within >12- 24 months with a frequency of 68 (37.99%), the majority of subject gained weight 2.2 kg with a frequency of 51 (28.9%), the longer use of DMPA injection (KB) on average the greater the weight gain. Test correlation with Kendall-tau (t) obtained p-value <0.000 (2.2x 10-16) (p-value <0.05), means that Ho rejected and there is an influence between duration of use DMPA injection (KB) to weight gain in Puskesmas Sewon I, Bantul in 2012 with a correlation coefficient of 0.5292, meaning that 54.92%, weight gain is influenced by KB injectable DMPA and 45.08% weight gai is influenced by other factors. There is enough influence with closeness between duration of use DMPA injection KB with weight gain in Puskesmas Sewon I, Bantul in 2012.